INTERNAL AUDIT EFFECTIVENESS IN THE INDONESIA PROPERTY INDUSTRY - Siahaan, Antonius TP; Tantono, Rudy (Emerging Markets : Business and Management Studies Journal, 2015)
The main purpose of this study is to analyze on the determinants of internal audit effectiveness in the public listed company in Indonesia specifically Top Ten Property Company by BCI Asia. Questionnaire was using for collecting data and distributed to the internal auditor and manager that has been audited by internal audit. The result of the study is to show the positive relation effects of Organizational Independence (OI), Formal Mandate (FM), Unrestricted Access (UA), Sufficient Funding (SF), Competent Leadership (CL), Objective Staff (OS), Competent Staff (CS), Stakeholder Support (SS) and Professional Audit Standards (PAS) with the internal audit effectiveness on the public listed company in Indonesia. The regreesion result shows OI, UA, SF, CL, OS, CS and SS have contributed for the internal audit effectiveness in the public listed company significantly and positively. The remaining two variable; FM and PAS were positively related with the IAE but their contribution for the IAE were statistically not significant. All of these nine independent variable are making 64% of the contributions for internal audit effectiveness in the public listed company.